In vitro determination of anti-lipidemic, anti-inflammatory, and anti-oxidant properties and proximate composition of range of millet types and sorghum varieties in Sri Lanka - Abeysekera, Walimuni Kanchana Subhashini Mendis; Jayathilaka, Sewwandi Indrachapa; Abeysekera, Walimuni Prabhashini Kaushalya Mendis; Senevirathne, Ilangasingha Gamlathge Nethmini Hansika; Jayanath, Nileththi Yasendra; Premakumara, Galbada Arachchige Sirimal; Wijewardana, Danthasingha Chithra Mulacharige Susantha Indika (Frontiers in Sustainable Food Systems, 2022)
Methanolic extracts of whole grains of five millet types and two sorghum varieties were evaluated for anti-lipidemic, anti-inflammatory, and a range of anti-oxidant properties in vitro (n = 3 each). Furthermore, proximate composition (n = 3 each) was also studied. Results showed significant differences (P < 0.05) among the selected samples for studied parameters. Pancreatic lipase and cholesterol esterase inhibitory activities of selected samples (2 mg/ml) ranged from 21.16 ± 1.58 to 66.65 ± 3.30 and 17.43 ± 0.60 to 52.09 ± 1.61%, respectively. Nitric oxide inhibitory activity of selected samples (2 mg/ml) ranged from −1.17 ± 0.32 to 13.56 ± 0.93%. Total polyphenolic content (TPC), total flavonoid content (TFC), and total proanthocyanidin content (TPAC) were in the range of 0.19 ± 0.01–12.50 ± 0.87 mg gallic acid equivalents/g, 0.05 ± 0.00–1.57 ± 0.01 mg quercetin equivalents/g, and 0.35 ± 0.01–12.87 ± 0.25 mg cyaniding equivalents/g of samples, respectively. Ferric reducing anti-oxidant power, oxygen radical absorbance capacity, ferrous ion chelating activity, and ABTS and DPPH anti-oxidant properties ranged from 0.15 ± 0.00 to 4.56 ± 0.03 mg of Trolox equivalents (TEs)/g, 0.19 ± 0.01 to 8.50 ± 0.72 mg of TEs/g, 0.13 ± 0.00 to 0.79 ± 0.03 mg EDTA equivalents/g, 0.22 ± 0.00 to 25.57 ± 0.35 mg of TEs/g, and 0.07 ± 0.00 to 22.97 ± 0.83 mg of TEs/g of samples, respectively. Among the studied samples, pigmented sweet sorghum exhibited the highest activities for all the tested parameters. The observed activities were moderate compared to the reference standards used. The highest values for proximate composition parameters tested varied with the different samples studied. In conclusion, the consumption of especially pigmented millet and sorghum in Sri Lanka may play an important role in the prevention and management of oxidative stress–associated chronic diseases. This is the first study to report pancreatic lipase and cholesterol esterase inhibitory activities of any millet types and sorghum varieties in Sri Lanka and the first report of cholesterol esterase inhibitory activity of millet and sorghum the world over.